2019
DOI: 10.1111/andr.12586
|View full text |Cite
|
Sign up to set email alerts
|

The epididymal amyloid matrix: structure and putative functions

Abstract: Background: We previously demonstrated the normal mouse epididymal lumen contains a non-pathological amyloid matrix that surrounds spermatozoa and plays important roles in sperm maturation and protection. Objective: The objective herein was to present a review of this work, including studies showing the amyloid structures of four members of the CRES (cystatin-related epididymal spermatogenic) subgroup are integral and essential components of the amyloid matrix. Methods: We used conformation-dependent reagents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…We hypothesize that cross-seeding may be conserved among other eukaryotic functional amyloid systems, as has been previously proposed for cystatin-related epididymal spermatogenic (CRES) proteins which form a functional amyloid matrix in the epididymal lumen of mice (32)(33)(34). While bacteria achieve nucleated polymerization by clustering minor and major amyloid subunits as individual genes within the same operon, we provide an example where the same mechanism is accomplished by alternative splicing.…”
Section: Discussionmentioning
confidence: 54%
“…We hypothesize that cross-seeding may be conserved among other eukaryotic functional amyloid systems, as has been previously proposed for cystatin-related epididymal spermatogenic (CRES) proteins which form a functional amyloid matrix in the epididymal lumen of mice (32)(33)(34). While bacteria achieve nucleated polymerization by clustering minor and major amyloid subunits as individual genes within the same operon, we provide an example where the same mechanism is accomplished by alternative splicing.…”
Section: Discussionmentioning
confidence: 54%
“…epididymis to one rich in fibrils in the distal epididymis (18). The epididymal amyloid matrix contains several family 2 cystatins of cysteine protease inhibitors, including cystatin C and four members of the CRES (cystatin-related epididymal spermatogenic) subgroup, a reproductive subgroup of family 2 cystatins (10).…”
mentioning
confidence: 99%
“…Previous studies have shown that 8 genes ( Cstl1 - Cstdc2 ) are located contiguously with Cst3 on chromosome 2 and are strongly expressed in the male reproductive tract (1719). Although CSTs are involved in the formation of the amyloid matrix that appears to function in maturation of spermatozoa in the epididymal lumen (20, 21), Cst8 or Cst9 single mutant male mice are fertile (22, 23). In this study, we generated mice lacking the entire male reproductive tract-specific CST family and examined the phenotypes of these cluster del mice.…”
mentioning
confidence: 99%